Study of prevalence of osteoporosis in males of above 40 years age group attending SMS Hospital, Jaipur - Qureshi, Parwez; Meena, R. C.; Husain, Jakir; Deshwar, Gaurav; Maheshwari, Vineet; Yadav, Lakhpat (International Journal of Research in Orthopaedics, 2017)
Background: Whenever osteoporosis is discussed, the focus is on women; men are far less likely to receive a diagnosis of osteoporosis or osteoporotic fracture because of considerable gaps in knowledge on male osteoporosis. The aim and objectives were to study the prevalence of osteoporosis in males of above 40 year age group attending SMS Hospital Jaipur & to explore the influence of various modifiable and non-modifiable risk factors on BMD. Methods: Study Location: SMS Medical College and Hospital, Jaipur. Study design: Hospital based cross sectional study. Study period: April 2015 to December 2016. Sample Size: 200. Work up: After taking ethical clearance and informed verbal consent, demographic and clinical details were noted along with S- calcium, Vitamin D and bone mineral density assessment. Osteoporosis was defined as T score ≤−2.5 bone mass −1 to −2.5 and normal as >−1. Data thus collected was analysed with help of SPSS 22.0 through frequency, percentages, Mean, SD and ANOVA. Results: Prevalence of osteopenia and osteoporosis in the study population was 28.5% and 11.5%. Age wise maximum prevalence was in the age group 71-80 years (31.81%). Prevalence of osteoporosis was more among Muslim community 20.83%, more in low socio economic group (BPL). T score of study population was -0.3705±1.41. The mean BMI, S-Calcium, Vitamin D levels and T score values among osteopenic and osteoporotic patients were statistically highly significant when compared to patients without osteo-penic/porotic changes (p<0.05). Conclusions: Osteoporosis is a silent killer and prevention is better than cure as prevention requires simple steps such as good dietary habits, active life style, good control of systemic disorders, reduced intake of tobacco and alcohol.